Implications of regulatory T cells in non-lymphoid tissue physiology and pathophysiology - Malko, Darya; Elmzzahi, Tarek; Beyer, Marc (Frontiers in Immunology, 2022)
Treg cells have been initially described as gatekeepers for the control of autoimmunity, as they can actively suppress the activity of other immune cells. However, their role goes beyond this as Treg cells further control immune responses during infections and tumor development. Furthermore, Treg cells can acquire additional properties for the control of tissue homeostasis. This is instructed by a specific differentiation program and the acquisition of effector properties unique to Treg cells in non-lymphoid tissues. These tissue Treg cells can further adapt to their tissue environment and acquire distinct functional properties through specific transcription factors activated by a combination of tissue derived factors, including tissue-specific antigens and cytokines. In this review, we will focus on recent findings extending our current understanding of the role and differentiation of these tissue Treg cells. As such we will highlight the importance of tissue Treg cells for tissue maintenance, regeneration, and repair in adipose tissue, muscle, CNS, liver, kidney, reproductive organs, and the lung.